2021
DOI: 10.1097/md.0000000000026104
|View full text |Cite
|
Sign up to set email alerts
|

Individual and combined effects of GSTM1, GSTT1, and GSTP1 polymorphisms on lung cancer risk

Abstract: Thirty-five previous meta-analyses have been reported on the individual glutathione S-transferase M1 ( GSTM1 ) present/null, glutathione S-transferase T1 ( GSTT1 ) present/null, and glutathione S-transferase P1 ( GSTP1 ) IIe105Val polymorphisms with lung cancer (LC) risk. However, they did not appraise the credibility and explore the combined effects between the 3 genes and LC risk. We performed a meta-analysis and re-analysis of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…It has been confirmed that the GSTM1 deletion genotype is associated with the occurrence of a variety of cancers. Studies have found that the GSTM1 deletion genotype is associated with increased lung cancer risk in Japanese and increased lung adenocarcinoma risk in Asians (15). At the same time, the study confirmed that GSTM1 gene deficiency combined with smoking increased the risk of cancer by 65% compared with the simple smoking group, indicating that GSTM1 gene deficiency and smoking have a synergistic effect on promoting the occurrence of lung cancer (16).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…It has been confirmed that the GSTM1 deletion genotype is associated with the occurrence of a variety of cancers. Studies have found that the GSTM1 deletion genotype is associated with increased lung cancer risk in Japanese and increased lung adenocarcinoma risk in Asians (15). At the same time, the study confirmed that GSTM1 gene deficiency combined with smoking increased the risk of cancer by 65% compared with the simple smoking group, indicating that GSTM1 gene deficiency and smoking have a synergistic effect on promoting the occurrence of lung cancer (16).…”
Section: Discussionmentioning
confidence: 63%
“…The change of genotype may affect the inactivation ability of individuals to carcinogens and increase the risk of cancer in some individuals exposed to the adverse environment (5). GSTM1 gene deletion has been reported to be associated with susceptibility to cervical cancer (6), lung cancer (7), nasopharyngeal carcinoma (8) and liver cancer (9). However, there are few reports on the susceptibility to GC and the prognosis of patients with GC.…”
Section: Introductionmentioning
confidence: 99%
“…We set a prior probability of 0.01, an OR of 1.50, and a FPRP cutoff value of 0.20 to select the most suitable gene model for predicting OC risk. 24 , 25 , 26 Only a significant result with a FPRP <0.20 was considered credible. Our results demonstrated that Fok1 rs2228570 was more strongly associated with OC risk than SRD5A2 rs523349, ST3GAL3 rs37460, miR‐146a rs2910164, and ERCC1 rs11615.…”
Section: Discussionmentioning
confidence: 99%
“…The FPRP analysis was used to assess significant associations. We set a prior probability of 0.01, an OR of 1.50, and a FPRP cutoff value of 0.20 to select the most suitable gene model for predicting OC risk 24‐26 . Only a significant result with a FPRP <0.20 was considered credible.…”
Section: Discussionmentioning
confidence: 99%